A child presenting with bullous emphysema - Özsezen, Beste; Özçelik, Uğur; Doğru, Deniz; Yalçın, Ebru; Orhan, Diclehan; Soyer, Tutku; Emiralioğlu, Nagehan; Nurullayev, Elnur; Özcan, H Nursun; Üner, Meral; Tural, Dilber Ademhan; Kiper, Nural (The Turkish Journal of Pediatrics, 2022)
Background. Placental transmogrification of the lung (PTL) is a clinical spectrum varying from asymptomatic to severe pulmonary impairment; such as recurrent pneumothorax, bronchopneumonia, respiratory distress syndrome and chronic obstructive airway disease. PTL usually presents as a bullous lesion, and rarely can appear in nodule or cyst formation on chest imaging. PTL with giant bullous emphysema has a male preference, is more commonly unilateral and mostly affects one lobe, but can rarely involve more than one lobe. Case. Here we report a 13-year-old boy presenting with bullous emphysema and coexisting with a borderline testicular tumor. He had no complaints of cough, sputum, or shortness of breath. He had a past medical history of pneumonia five years ago. In order to elucidate the underlying lung pathology, a wedge lung biopsy was performed and the patient was diagnosed with PTL. Scrotum ultrasonography was performed because of hydrocele in both testes, and bilateral epididymal cysts with papillary solid projections were reported. Pathological examination of the epididymal tumor revealed a `Mullerian type borderline epithelial neoplasm` which is an analogue of the ovarian serous borderline tumor. Conclusions. In conclusion, we reported the youngest PTL case in the literature, a rare disease with unknown pathophysiology, presenting as bullous emphysema and coincidental Mullerian type borderline epithelial neoplasm. It is important to diagnose placental transmogrification of the lung in a child with bullous emphysema because compared to other cystic lung diseases it is a benign disease and if no additional malignity exists, lobectomy or pneumonectomy is the cure for the disease.